Analisa & Perancangan Edukasi Keamanan Berlalu Lintas bagi Masyarakat Berbasis Konten Multimedia Animasi - Zulfan Zulfan; Samsuddin Samsuddin (Fakultas Teknik, 2016)
The population addition in Indonesia has become so significant that it becomes one of factor for number of vehicles increasing that will ultimately add to the number of violations in road traffic. It is also caused by a lack of understanding and awareness ofroad users that obey the rules so as to improve safety in road traffic. This research aims to create and design multimedia content that will serve as an information medium traffic safety for road users based 2D animation. In this multimedia content will be presented how things happen on the highway, especially at the traffic light and causal arise if the road users do not comply with regulations in road traffic. The results of this research is multimedia products 2D animation about traffic safety. The results of this study can be used to convey information to road users and also become material for early childhood education. The results of this study can also be used as a model to enrich the scientific learning and teaching materials in Multimedia Systems course for students in the Department of Information Engineering University of Serambi Mekkah